2006
DOI: 10.1038/sj.cr.7310014
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a new actin-binding region in p57

Abstract: The actin-binding protein p57 is a member of mammalian coronin-like proteins. The roles of this protein in phagocytic processes conceivably depend on its interactions with F-actin. Two regions, p571-34 and p57 , were previously reported to be actin-binding sites. In this study, we found that the C-terminal region of p57, p57 , also possessed F-actin binding activity. Furthermore, the leucine zipper domain at the C-terminus of p57 was essential for this actin-binding activity. The F-actin cross-linking assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Previous studies indicated that full-length CRN2 possesses binding sites for F-actin in the conserved WD40-repeat domain forming the seven-bladed β-propeller659 and in the conserved part of the C-terminal linker region34596061. More specifically, a conserved arginine residue, R30 in CRN1 and R28 in CRN2, which is surface exposed and located within the seventh β-propeller blade3, has turned out to be essential for F-actin binding of both coronin proteins1262.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that full-length CRN2 possesses binding sites for F-actin in the conserved WD40-repeat domain forming the seven-bladed β-propeller659 and in the conserved part of the C-terminal linker region34596061. More specifically, a conserved arginine residue, R30 in CRN1 and R28 in CRN2, which is surface exposed and located within the seventh β-propeller blade3, has turned out to be essential for F-actin binding of both coronin proteins1262.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to the actin-binding mechanism of CORO1A (also known as coronin-like protein p57), a member of the coronin family. F-actin-binding of CORO1A through the C-terminus (CT, 297-461) requires a functional leucine zipper situated in a short dimerization/ trimerization domain (CC, 432-461) (Liu et al, 2006). In addition to the direct F-actin binding, coupling of CMS or CIN85 to F-actin via cortactin (Lynch et al, 2003), Alix/AIP1 (Chen et al, 2000), or CapZ (Hutchings et al, 2003) adds a layer of complexity and probably regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This structure includes two cryptic blades that flank the five known WD40 repeats and a Cterminal extension that folds tightly along the bottom of the ␤-propeller. Many of the earlier attempts to map the F-actinbinding site of coronin used truncation mutants that contained fragments of this compact structure (Gatfield et al, 2005;Liu et al, 2006;Mishima and Nishida, 1999;Oku et al, 2003;Spoerl et al, 2002). These fragments may not adopt stable or physiological conformations and the results of these studies must be confirmed using mutations in the full-length protein (Appleton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%